2022
DOI: 10.4314/iijikm.v12i2.2
|View full text |Cite
|
Sign up to set email alerts
|

Staff Attitude and Service Delivery in University Libraries in Ogun State, Nigeria

Abstract: Service delivery in the university library is aimed at meeting the information need of users who make up the university community in order to achieve the objective of promoting learning and research. Services delivery of university libraries in the aspect of tangibles and reliability will bring satisfaction to the recognised need of the users. Staff attitude goes a long in library service delivery influences the patronage of the library resources. This study adopted survey research design.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Therefore, the importance of librarians' attitudes on library patronage cannot be overemphasized. This finding agrees with Oden and Owolabi (2021) who found out that staff attitude had a significant influence on service delivery. In the same vein, Idowu and Oso (2022) findings also revealed that perception of undergraduates about library service quality and satisfaction with services offered by librarians had relationship with librarians' image.…”
Section: Discussion Of Findingssupporting
confidence: 92%
See 3 more Smart Citations
“…Therefore, the importance of librarians' attitudes on library patronage cannot be overemphasized. This finding agrees with Oden and Owolabi (2021) who found out that staff attitude had a significant influence on service delivery. In the same vein, Idowu and Oso (2022) findings also revealed that perception of undergraduates about library service quality and satisfaction with services offered by librarians had relationship with librarians' image.…”
Section: Discussion Of Findingssupporting
confidence: 92%
“…This suggested that the undergraduates have positive attitude towards the library staff. This finding is in line with earlier study by Oden and Owolabi (2021) who examined the influence of staff attitude on service delivery in university libraries in Ogun State, Nigeria. Their findings revealed that the respondents affirmed that the library staff delivered quality services and their staff attitude was positive.…”
Section: Discussion Of Findingssupporting
confidence: 92%
See 2 more Smart Citations
“…The effectiveness of library services is measured by the competency of the librarian as well as the availability of current information services in providing efficient and effective services in academic libraries [12]. The introduction of information communication technology in library services has again helped in eliminating the bottleneck and cumbersomeness associated with manual library service.…”
Section: Utilization Of Library Services By Undergraduatesmentioning
confidence: 99%